Assessment of cardio-oncology knowledge and practice among healthcare providers in Saudi Arabia: a comprehensive nationwide survey - Hisham A. Badreldin; Nada Alsuhebany; Lama Alfehaid; Mohammed Alzahrani; Maha Aldoughaim; Abdullah M. Alrajhi; Jumanah Alsufyani; Dania Elsherif; Kanan Alshammari (Cardio-Oncology)
Abstract Introduction The evolving field of oncology necessitates effective management of cancer-related cardiovascular diseases. In Saudi Arabia, the incidence of cancer is rising, and there is a critical need for cardio-oncology services to address cancer treatment-related cardiovascular toxicity. This study aimed to evaluate the knowledge and practices of healthcare providers (HCPs) in Saudi Arabia regarding cardio-oncology. Methods A cross-sectional study was conducted from January 2024 to April 2024 using an online survey targeting cardiologists, oncologists, and clinical pharmacists. The survey assessed demographics, perceptions of cardio-oncology, availability of services, and current practices. Data were analyzed using descriptive statistics, chi-squared tests, and bivariate analyses. Results The survey received responses from 116 HCPs, including cardiologists (63.79%), oncologists (23.28%), and clinical pharmacists (12.93%). Most participants had over six years of experience, and only one had formal cardio-oncology training. While 84.48% recognized the importance of managing cardiac complications in cancer patients, only 42.24% were familiar with existing guidelines. Limited training programs and institutional resources were significant barriers to implementing cardio-oncology services. Despite agreement on the need for cardiotoxicity management, only one-third recommended cardioprotective agents as standard care. Conclusion There is a notable deficiency in formal training and resources for cardio-oncology in Saudi Arabia. To bridge this gap, integrating cardio-oncology into training programs, establishing institutional guidelines, and adopting multidisciplinary care models are crucial. These measures will enhance the quality of care for cancer patients and improve their cardiovascular outcomes.